Antigenic differences between human platelets and megakaryocytes. - Hyde, P. (1987)
To investigate the apparent paradox in the observation that most patients with immune thrombocytopenias have normal or increased numbers of megakaryocytes (MKs), the extent of antigenic cross-reactivity between normal platelets and MK was examined. Indirect immunofluorescence and ultrastructural studies were carried out by means of four antisera specific for platelets: anti-GpIb, anti-GpIIb/IIIa, anti-PLA1, and an antiserum from a patient with quinidine-induced thrombocytopenia. Following incubation of freshly collected marrow with these antisera, MK were first identified by phase-contrast microscopy and then inspected for fluorescence. Almost all MKs were found reactive with the last three antisera, albeit to a variable extent. In contrast, only 24% reacted with anti-GpIb. The pattern of fluorescence, ie, rim, partial or cytoplasmic, appeared to be related to the extent of MK fragmentation. Only rim fluorescence of living MKs could be interpreted to indicate that the platelet epitope was exposed on the surface of the precursor cell. The observations suggest that platelet antigens are variably expressed on the plasma membranes of MKs. In a clinical setting, the heterogeneity among platelet target antigens and the extent to which these are exposed on MKs at various stages of maturation may dictate the severity of the thrombocytopenia and degree of ineffective thrombocytopoiesis.